1999
DOI: 10.1093/jjco/29.2.58
|View full text |Cite
|
Sign up to set email alerts
|

Messenger RNA Expression of Matrix Metalloproteinases and Tissue Inhibitors of Metalloproteinases in Human Hepatocellular Carcinoma

Abstract: Our results suggest that semiquantitative RT-PCR analysis of MMPs may be helpful in disease management of patients with hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…23,29 It has been reported that an imbalance of MMPs and TIMPs can induce or exacerbate several diseases. 8,9 We noted that, in the bowel of UC patients, the overexpression of MMPs, mainly matrilysin, and the hypoexpression of TIMPs were observed. These observations are consistent with previous reports.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…23,29 It has been reported that an imbalance of MMPs and TIMPs can induce or exacerbate several diseases. 8,9 We noted that, in the bowel of UC patients, the overexpression of MMPs, mainly matrilysin, and the hypoexpression of TIMPs were observed. These observations are consistent with previous reports.…”
Section: Discussionmentioning
confidence: 97%
“…These observations are consistent with previous reports. 8 It is noteworthy that the reduced expression of TIMPs compared with the expression of matrilysin, is related to severe inflammation grades. The use of matrilysin as a molecular marker may become a routine part of the management of patients with UC, thus helping to define appropriate therapeutic and follow-up protocols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Waas et al [17] concluded that the preoperative plasma proMMP-2, proMMP-9 and TIMP-1 levels have no potential as diagnostic or prognostic marker in CLM. In 1999, Yamamoto et al [26] reported that increased mRNA expression of TIMP-1 and TIMP-2 was observed in tumor tissue in half of the patients with hepatocellular carcinoma, but did not correlate with any clinicopathological features using semiquantitative RT-PCR for mRNA determination. We used quantitative RT-PCR, and found that the mRNA level of TIMP-1 expression was statistically significantly associated with DFI and OS.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, expression of activated MMP-2 is related to regional lymph node and distal metastasis as well as to postresection recurrence of the same tumour. 56 Concomitant overexpression of MMP-2 and MMP-7 is associated with recurrence in hepatocellular cancer, 57 and elevated MMP-9 expression in tumor cells is related to recurrence in superficial carcinoma of the urinary bladder. 58 The expression of certain MMPs in primary tumour can predict the risk of metastasis.…”
Section: Mmps As Predictors Of Recurrence or Metastasis Riskmentioning
confidence: 99%